2020
DOI: 10.1038/s41375-020-0792-2
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-cells that target acute B-lineage leukemia irrespective of CD19 expression

Abstract: Chimeric antigen receptor (CAR) T-cells targeting CD19 demonstrate remarkable efficacy in treating B-lineage acute lymphoblastic leukemia (BL-ALL), yet up to 39% of treated patients relapse with CD19(−) disease. We report that CD19(−) escape is associated with downregulation, but preservation, of targetable expression of CD20 and CD22. Accordingly, we reasoned that broadening the spectrum of CD19CAR T-cells to include both CD20 and CD22 would enable them to target CD19(−) escape BL-ALL while preserving their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 55 publications
3
95
1
Order By: Relevance
“…After promising in vitro studies which showed success in targeting CD19− escape B-ALL cells, in vivo mouse models were used to investigate the efficacy of CD19/20/22 CAR T cell therapy on targeting CD19+ and CD19− escape malignancies. Treatments of CD19/20/22 CAR T cells showed significant anti-tumour response in both mouse models with CD19+ B-ALL as well as the CD19− escape B-ALL which CD19 CAR T cells was ineffective at treating alone [24]. This method presents an exciting branch of CAR T cell therapy for haematological B cell malignancies which do not express CD19.…”
Section: Limitations Of Car T Cell Therapy For Haematological Cancersmentioning
confidence: 94%
“…After promising in vitro studies which showed success in targeting CD19− escape B-ALL cells, in vivo mouse models were used to investigate the efficacy of CD19/20/22 CAR T cell therapy on targeting CD19+ and CD19− escape malignancies. Treatments of CD19/20/22 CAR T cells showed significant anti-tumour response in both mouse models with CD19+ B-ALL as well as the CD19− escape B-ALL which CD19 CAR T cells was ineffective at treating alone [24]. This method presents an exciting branch of CAR T cell therapy for haematological B cell malignancies which do not express CD19.…”
Section: Limitations Of Car T Cell Therapy For Haematological Cancersmentioning
confidence: 94%
“…There are two patterns of trivalent CAR T-cells: TriCAR expressing CD19 CAR, CD20 CAR, and CD22 CAR on a single T-cell and side CAR expressing CD20/CD19 TanCAR combined with CD19 CAR ( 31 ). Fousek et al ( 172 ) constructed CD19/CD20/CD22 TriCAR T-cells that manifested strong killing activity on both ALL cells and CD19-negative relapsed cells in vitro and in murine models, while CD19 CAR T-cells were ineffective.…”
Section: Clinical Strategiesmentioning
confidence: 99%
“…Indeed, one 8-year old patient received sequential treatments of anti-CD19 CAR, followed by anti-CD22 CAR resulting in partial response, subsequently followed by anti-CD20 CAR which cleared the cancer to complete remission [ 34 ]. Rather than giving each of these treatments sequentially, a recent CAR construct was designed to transduce donor T-cells with CD19, CD20 and CD22 targeting CARs in the same cell [ 35 ], thus cells that lose expression of one of the lineage markers would still be cleared by the adoptively transferred CARs.…”
Section: Loss Of Car Antigenmentioning
confidence: 99%